Pengaruh Profitabilitas Terhadap Harga Saham PadaPerusahaan Perbankan Yang Terdaftar Di BEI PeriodeTahun 2012 Sampai Dengan Tahun 2015 - Dewi, Wulan Kurnia, Drs. Agus Muqorrobin, MM (2017)
This study aims to determine the effect of profitability is measured by Return on Assets (ROA) and Return On Equity (ROE) of the share price on the banking companies listed in Indonesia Stock Exchange (BEI). The population of this research is the Banking Companies Listed in Indonesia Stock Exchange (BEI) in the period 2012 to 2015. The samples in this study using purposive sampling so obtained 9 samples Banking Company. The data used was obtained from the secondary www.idx.co.id. The analytical method used is multiple regression analysis. The calculation result AjdustedR² value equal to 0,531. It shows that 53.1% of the company's stock price variation can be explained by the amount of ROA and ROE. While the remaining 36.9% is explained by other variables outside the model used in this study.